ANALISIS TIME AND MOTION: EFISIENSI BEBAN KERJA DIRECT MARKETING DI ERA DISRUPSI DIGITAL - Asaretkha Adjane Annisawati; Imam Kambali; Rahmat Tri Yuli Yanto (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2021)
The purpose of this research is to determine the sequence of Direct Marketing work processes before and after the Fourth Industrial Revolution. The Time and Motion Study method is used to assess the burden of Direct Marketing officers in all aspects of their duties in the Digital Disruption Era. This study's data was gathered through observations, interviews, and